The Spread of Non-native Plant Species Collection of Cibodas Botanical Garden into Mt. Gede Pangrango National Park - Zuhri, Musyarofah; Mutaqien, Zaenal (Journal of Tropical Life Science, 2013)
The role of botanic garden in spread of non-native plant species has concerned of international worldwide. This study aimed to study the extent of non-native plant species from Cibodas Botanical Garden (CBG) which invades into natural rainforest. A line transect was made edge-to-interior with 1,600 m in distance from CBG boundary. Result showed that distance from CBG was not significant in correlation with non-native tree and treelet density. Furthermore, presence of existing CBGs plant collection was not a single aspect which influenced presence and abundance. Three invasive species possibly was escape from CBG and it showed edge-to-interior in stems density, i.e. Cinchona pubescens, Calliandra calothyrsus and Cestrum aurantiacum. The patterns of non-native species were influenced by presence of ditch across transect, existence of human trail, and the other non-native species did not have general pattern of spread distribution. Overall, botanical gardens should minimize the risk of unintentional introduced plant by perform site-specific risk assessment.